Developing a multi-objective simulation-optimization model for ecological water conveyance in arid inland river basins - Qiang Han; Lianqing Xue; Yuanhong Liu; Mingjie Yang; Xinyi Chu; Saihua Liu (Journal of Hydrology: Regional Studies, 2023)
Study region: Middle and lower reaches of Tarim River, southwestern of Xinjiang Province, China. Study focus: Ecological water conveyance is an important measure to protect the fragile ecosystem of inland rivers in arid areas. This paper attempted to present a integrated model for optimal ecological water conveyance scheme (EWCS). In this model, the impact of the duration of water conveyance and the water allocation of each channel on the groundwater level was considered. The optimized ecological water conveyance scheme can simultaneously maximize groundwater level rise value (GLRV) and minimize ecological water conveyance volume (EWCV). New hydrological insights for the region: An simulation-optimization model was proposed based on MODFLOW model, Kriging surrogate model and NSGA-II. The study obtained the Pareto frontiers of EWCS in three typical years (dry, normal and wet), and made decisions using the TOPISIS-Entropy method. The scenario comparison results indicated that the optimized EWCS requires less EWCV than the existing one when achieving the same GLRV, proving that the optimized EWCS has higher water resource utilization efficiency. This simulation-optimization model fills the research gap of EWCS in arid inland river basins and provides scientific guidance for government management.